Preparation, morphology and superior performances of biobased thermoplastic elastomer by in situ dynamical vulcanization for 3D-printed materials. (13th January 2017) - Hu, Xiaoran; Kang, Hailan; Li, Yan; Geng, Yiting; Wang, Runguo; Zhang, Liqun
Abstract: 3D-printing of polymers provides the opportunity to fabricate materials into customized sizes and shapes. The present study describes fully renewable thermoplastic vulcanizates (TPVs) consisting of synthesized biobased elastomer (PLBSI) and poly (lactic acid) (PLA) by in situ dynamic vulcanization for 3D-printed materials. The morphology study implied in situ dynamic vulcanization and phase inversion occurs and leads the PLBSI elastomer dispersed as microparticles in PLA matrix. Then, the morphological evolution mechanism was proposed and indicated the dispersed PLBSI elastomer microparticles are actually agglomerates of elastomer nanoparticles. The PLBSI/PLA TPVs perform good processability and reprocessability by rheological and recyclability tests. Besides, good in vitro degradability and cytotoxicity suggests PLBSI/PLA TPVs are promising sustainable biomaterials. The superior strength and elasticity confirmed by the tensile tests of 3D-printed samples, and firm microstructure and the reliable printed accuracy of 3D-printed samples investigated by SEM implied the PLBSI/PLA TPVs were ideal 3D-printing materials. Graphical abstract: Highlights: Fully renewable TPVs consisting of synthesized biobased elastomer and PLA by in situ dynamic vulcanization are prepared. The morphology study proves phase inversion occurred during the dynamic vulcanization process. The TPVs own renewable origins, good processability and reprocessability, excellent degradability and biocompatibility. The superior 3D-printed performances indicate the TPVs is ideal 3D-printing biomedical materials.